Integration of metabolomic and transcriptomic profiling to compare two protocols of differentiation of human induced pluripotent stem cells into hepatocytes. (January 2020) - Jellali, Rachid; Poulain, Stephane; Bernier, Myriam Lereau; Gilard, Françoise; Tauran, Yannick; Kato, Sachi; Danoy, Mathieu; Segard, Bertrand David; Kido, Taketomo; Miyajima, Atsushi; Plessy, Charles; Sakai, Yasuyuki; et al.
Graphical abstract: Highlights: Induced pluripotent stem cells iPSC differentiation to hepatocytes was characterized. Two protocols were studied and compared to reduce the cost of differentiation. Metabolomics analyses were coupled with Cap Analysis Gene Expression (nanoCAGE). Hepatic phenotype was confirmed in both protocols by albumin and urea production. Omics analyses explained iPSC metabolism during step-by-step differentiation. Abstract: Human hepatocyte-like cells derived from human induced pluripotent stem cells (hiPSC) may provide an unlimited supply of cells for in vitro liver models. However, hiPSC differentiation remains a major challenge due to immaturity of the hepatocytes obtained and the high cost of differentiation protocols currently proposed. Here, we studied the efficacy of new protocol, with reduction of growth factors, for the generation of hepatocyte-like cells from hiPSC. We performed metabolomic and mRNA analysis by RTqPCR and nanoCAGE processing to identify and understand key metabolisms during differentiation. By reducing the change frequency of the culture medium in the new protocol, we successfully generated hepatocyte-like cells producing albumin, urea, and CYP3A4 positive. The metabolomic analysis successfully extracted both signatures, common and specific, for each differentiation step. Integrating the metabolomic data with transcriptomic contributed to explaining the kinetics of carbohydrate, lipid and nitrogen metabolism throughout differentiation. The information extracted during differentiation showed that the cells moved from an aerobic-like respiration pattern to a mitochondrial oxidative respiration pattern in both protocols. Reducing culture medium renewal led to reduced glucose consumption, followed by fructose production and significant extracellular lipogenesis throughout differentiation. We believe that the overall dataset can provide information on the sequence of process.